IPAS Learning Transformation: A Development Study of Portfolio-Based Mind Mapping to Enhance Critical Thinking - Christina Switaningsih handayani; Ngatmini; Joko Siswanto (Jurnal Ilmiah Sekolah Dasar, 2026)
Science and Social Studies (IPAS) learning in primary schools plays an important role in helping students understand natural and social phenomena contextually. However, in practice, learning is still dominated by conventional approaches that emphasize memorization, which limits the development of critical thinking skills. This study aims to analyze the validity, practicality, and effectiveness of a portfolio-based mind mapping learning model in enhancing students’ critical thinking skills. This research is a development study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects included content experts, media experts, education practitioners, and primary school students as product users. Data were collected through questionnaires and tests, with instruments consisting of validation sheets, response questionnaires, and critical thinking skill tests. Data were analyzed using quantitative descriptive, qualitative descriptive, and inferential statistical techniques. The results show that the developed learning model has a very high level of validity, with scores ranging from 90% to 94%, and is proven to be practical and effective based on statistical test results indicating a significant improvement in students’ critical thinking skills. Therefore, the portfolio-based mind mapping learning model is feasible as an innovative alternative in IPAS learning. The implication of this study is that the developed model can support teachers in creating learning environments that foster students’ critical thinking skills.